Solubility and preferential solvation of some n-alkyl-parabens in methanol + water mixtures at 298.15 K (2017)
Methyl, ethyl and propyl parabens equilibrium solubility was determined in (methanol + water) binary mixtures at 298.15 K. The mole fraction solubility of these compounds increased in 503 (from 2.40 × 10-4to 0.121), 1377 (from 9.86 × 10-5to 0.136) and 4597 (from 3.73 × 10-5to 0.171) times when passing from neat water to neat methanol, for methyl, ethyl and propyl parabens, respectively. All these solubility values were correlated with the Jouyban-Acree model. Preferential solvation parameters by methanol (dx1,3) of these parabens were derived from their thermodynamic solution properties using the inverse Kirkwood-Buff integrals (IKBI) method. For all compounds dx1,3values are negative in water-rich mixtures but positive in mixtures with methanol mole fraction greater than 0.32. It is conjecturable that in the former case the hydrophobic hydration around non-polar groups of parabens plays a relevant role in the solvation. Besides, the preferential solvation of these solutes by methanol in mixtures of similar co-solvent compositions and in methanol-rich mixtures could be explained in terms of the higher basic behaviour of methanol. © 2017 Elsevier Ltd